Communication Strategy of Relationship Chat Account Manager in Managing the Follower - Anna Gustina Zainal; Toni Wijaya; Andy Corry Wardhani (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2021)
Each social media account created by users has its own purpose and meaning,. That is to attract the sympathy of the audience, Just like in real world, humans cannot live without socializing and interacting each other. This research was designed to find out the communication strategy of social media account managers in managing followers. This study used an interactional communication strategy with qualitative descriptive method. The results showed that the communication strategy used to manage the "chat relationship" account is the interactional communication strategy. This model had been used because followers have different backgrounds, knowledge, experiences, and cultures that affect each person in interpreting message. There are many factors as key success to running an online-based business through social media "relationships chat" account in order to increase followers loyalty in accordance with the strategy adopted by the account managers. Several management strategies had been applied such as a presentation to the audience, audience segmentation, consistency in providing entertainment to the audience, consistency of the characteristics and features needed, constantly looking for the latest entertainment innovations, communicating directly with consumers to support activities, and creating cooperation between account managers are being the key success to gain sympathy and loyalty from followers.